2014
DOI: 10.1063/1.4863836
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and microinstabilities at perpendicular collisionless shock: A comparison of large-scale two-dimensional full particle simulations with different ion to electron mass ratio

Abstract: Large-scale two-dimensional (2D) full particle-in-cell simulations are carried out for studying the relationship between the dynamics of a perpendicular shock and microinstabilities generated at the shock foot. The structure and dynamics of collisionless shocks are generally determined by Alfven Mach number and plasma beta, while microinstabilities at the shock foot are controlled by the ratio of the upstream bulk velocity to the electron thermal velocity and the ratio of the plasma-to-cyclotron frequency. Wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…The process is called a cyclic self-reformation of the shock and is caused by the dynamics of the shock-reflected ions (see, e.g., Treumann 2009; Umeda et al 2010Umeda et al , 2014. Figure 18 shows the time evolution of the average density profile in the vicinity of the forward shock.…”
Section: Shock Reformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is called a cyclic self-reformation of the shock and is caused by the dynamics of the shock-reflected ions (see, e.g., Treumann 2009; Umeda et al 2010Umeda et al , 2014. Figure 18 shows the time evolution of the average density profile in the vicinity of the forward shock.…”
Section: Shock Reformationmentioning
confidence: 99%
“…For panel (b), we compensated the average velocity of all ions (see Figure 10), whereas for panel (c) on the right we compensated only the average motion of incoming ions. Umeda et al 2009Umeda et al , 2010Umeda et al , 2014. The ion temperature anisotropy arising from ion reflection at the shock can drive the Alfvén ion cyclotron (AIC) or the mirror instability in the shock ramp, and the resulting unstable modes have wavelengths of a few ion skin depths and propagate along the regular magnetic field, significantly contributing to ion isotropization and thermalization at the shock and downstream.…”
Section: Structure Of the Reverse Shockmentioning
confidence: 99%
“…The MTSI was dominant in the foot region in the runs with m i /m e = 100, 256, and 625 (Umeda et al, 2012b(Umeda et al, , 2014. The excitation of the whistler mode in the foot region was also indicated by the enhancement of the shock magnetic field at the timescale much shorter than the local ion cyclotron period.…”
Section: Discussion On the Simulation Resultsmentioning
confidence: 81%
“…The excitation of the whistler mode in the foot region was also indicated by the enhancement of the shock magnetic field at the timescale much shorter than the local ion cyclotron period. It was also shown that the wavelength in the shock tangential direction of the whistler mode excited by the MTSI is close to the wavelength of the ripples (Umeda et al, 2014). It is suggested that wave-wave coupling between the whistler mode and the ripples is possible, which disturbs the periodic reformation of (quasi-)perpendicular shocks.…”
Section: Discussion On the Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation